PENGARUH ENVIRONMENTAL, SOCIAL, GOVERNANCE (ESG) DISCLOSURE DAN TOTAL ASSET TURNOVER (TATO) TERHADAP NILAI PERUSAHAAN - Saputra B, Rizky; Mei Susilowati, Pusvita Indria (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2025)
This study aims to test and analyze the Influence of Environmental, Social, Governance (ESG) Disclosure and Total Asset Turnover (TATO) on Company Value. This research was conducted on industrial sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The population of this study is 54 companies in the industrial sector listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The sample selection used a purposive sampling method with certain criteria, which resulted in 18 companies that met the criteria with a span of 3 years, so that the total sample used in the study was 54 samples. The analysis model used is panel data regression through Econometric View 12 (EViews 12). The results of this study show that environmental disclosure, and social disclosure have no effect on company value, while governance disclosure has a negative effect on company value, and total asset turnover has a positive effect on company value